PENINGKATAN PELAYANAN BISNIS PADA IKM KOMPONEN OTOMOTIF DI CIKARANG KABUPATEN BEKASI - Agung Edi Rustanto; Donny Oktavian Syah; Setiawan Setiawan; Shufi Muhammad (JURNAL LENTERA BISNIS, 2024)
PT Nikko Teknik Indonesia is a tier-3 Small and Medium Industry company which operates in the field of manufacturing automotive components in the city of Bekasi. Tier-3 companies are automotive component manufacturing companies at the lowest level, such as PT Nikko Teknik Indonesia which focuses on making jigs, dies and welding from automotive components. The urgency of this research, there are many obstacles faced by tier-3 companies such as lack of use of technology information to support business, marketing aspects. It often managed conventionally (so it difficult to get new buyers/vendors) and also problems with automation of tracking components which deliver to customer. So, implementing comprehensive supply chain management e-dashboard is very helpful for tier-3 automotive component SME’s businesses. The research methods used are Data Envelopment Analysis (DEA) and Rapid Development Application (RAD) methods in automotive component production companies. The results of this research are that it has succeeded in building an e-Dashboard system for Supply Chain Management recording information, which provides facilities: statistics and indicators starting from raw materials, work-in-process and finished goods that are ready to be sent to buyers. . Keywords: Automotive Components SMEs, Business Services, E-Supply Chain Management